Studi Kelayakan Investasi Proyek Pembangunan Pembangkit Listrik Tenaga Uap PLTU Riau 2x110 MW Studi Kasus : Proyek PLTU Riau 2x110 MW Pekanbaru - Febrian, Aris; Iriana, Rian Tri Komara; Malik, Alfian (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Project PLTU RIAU 2x110 MW is located in Tenayan Raya regency, Pekanbaru, Riau province. The project proposed to support energy demand especially for Riau Province in line to support a national program in order to increase national electricity ratio. This projectneeds high funding to construct therefore, it is necessary for the Government to study and analyze some aspects including financial. 30 % of the project funds came from PT PLN (Persero) equity equal to Rp995.646.470.749,47 while the other 70% which isRp2.323.175.098.415,43 came from loan. Feasibility analysis represents that Net Present Value (NPV) is Rp515.754.288.356,69, Benefit Cost Ratio is 1,05, Internal Rate of Return is12.62%, whereas Payback period is 16 years and 3 months, it represents that this project is feasible. The sensitivity analysis showed that the investment will be sensitive at 177,26%, thebenefit will be sensitive at 93%, the cost at 109% from the original value, and interest will be sensitive at 12,62%. As per deterministic sensitivity analyses from the several variables indicated that the highest to lowest influences in sequence is (1) tariff, (2) r class tariff, (3) operational and maintenance cost, (4) exchange rate, and as per the regression value also indicated that (1) tariff, (2) r class tariff, (3) operational and maintenance cost, (4) exchange rate, has the effect from the highest to lowest variable.Keywords: Finansial Analisys, Net Present Value, Benefit Cost Ratio, Internal Rate of Return, Payback period, Sentivity Analysis.